The Synthesis and Characterization of a Novel One-Dimensional Bismuth (III) Coordination Polymer as a Precursor for the Production of Bismuth (III) Oxide Nanorods - Hanifehpour, Younes; Mirtamizdoust, Babak; Dadashi, Jaber; Wang, Ruiyao; Rezaei, Mahboube; Abdolmaleki, Mehdi; Joo, Sang Woo (Crystals (Basel), 2022)
A novel Bi (III) coordination compound, [Bi(HQ)(Cl)4]n ((Q = pyridine-4-carbaldehyde thiosemicarbazone), was prepared in this research using a sonochemical technique. SEM, infrared spectroscopy (IR), XRD, and single-crystal X-ray analysis were utilized to analyze the Bi(III) coordination compound. The structure determined using single-crystal X-ray crystallography indicates that the coordination compound is a 1D polymer in solid state and that the coordination number of bismuth (III) ions is six, (BiSCl5), with one S donor from the organic ligand and five Cl donors from anions. It is equipped with a hemidirectional coordination sphere. It is interesting that the ligand has been protonated in the course of the reaction with a Cl- ion balancing the charge. This compound’s supramolecular properties are directed and regulated by weak directional intermolecular interactions. Through π–π stacking interactions, the chains interact with one another, forming a 3D framework. Thermolysis of the compound at 170 °C with oleic acid resulted in the formation of pure phase nanosized Bi (III) oxide. SEM technique was used to examine the morphology and size of the bismuth (III) oxide product produced.